(untitled) (Boston, 1993)
Contains ancillary and online exclusive content, drawing from the expertise of the distinguished Cleveland Clinic faculty. Taking a more clinical approach than other review texts, this practical resource includes a unique and well-structured set of exercises that offer a challenge at the end of each chapter
Keywords: Internal medicine,Internal medicine,Y khoa quốc tế,Y khoa quốc tế